PEMBELAJARAN SEJARAH DI THAILAND - Mantab, Porntip; Wijaya, Daya Negri (Jurnal Pendidikan Sejarah Indonesia, 2024)
Abstract: The aim of this research is to explore the current state of history education in Thailand. The research method employed is library research. Findings indicate that history education in Thailand is characterized by an emphasis on learning about historical events and developing an understanding of the nation's past. Teaching methods and approaches often prioritize reading and discussing significant historical events. One method of teaching is by emphasizing active learning, which takes various forms such as Brainstorming, Problem/Project/Case Study-based Learning, Games-based Learning, and others. The goal is to develop students' problem-solving skills and apply knowledge practically. Furthermore, knowledge acquisition is facilitated through student experiences and summaries. Various media tools like illustrations, videos, and storytelling are also utilized to enhance comprehension and enrich learning experiences. History education also emphasizes the development of analytical skills, including the examination of event origins and impacts, and encourages students to derive lessons from experiences and documentaries to create diverse and meaningful learning encounters relevant to their daily lives. Abstrak: Tujuan dari penelitian ini adalah untuk menyelidiki kondisi pendidikan sejarah saat ini di Thailand. Metode penelitian yang digunakan adalah penelitian perpustakaan. Temuan menunjukkan bahwa pendidikan sejarah di Thailand ditandai dengan penekanan pada pembelajaran tentang peristiwa sejarah dan pembangunan pemahaman tentang masa lalu negara. Metode pengajaran dan pendekatan pembelajaran seringkali memprioritaskan membaca dan mendiskusikan peristiwa sejarah yang signifikan. Salah satu cara mengajar adalah dengan menekankan pada pembelajaran aktif yang memiliki berbagai macam bentuk seperti Brainstorming, Pembelajaran Berbasis Masalah/Proyek/Studi Kasus, Pembelajaran Berbasis Permainan, dan lain-lain. Tujuannya adalah untuk mengembangkan kemampuan siswa dalam memecahkan masalah dan menerapkan pengetahuan secara praktis. Selain itu, pengetahuan juga diperoleh melalui pengalaman dan ringkasan dari para siswa. Selain itu, berbagai media seperti ilustrasi, video, dan penceritaan digunakan untuk memperkaya pemahaman dan meningkatkan pengalaman belajar. Pendidikan sejarah juga menekankan pengembangan keterampilan analitis, termasuk pemeriksaan asal-usul dan dampak peristiwa, dan mendorong siswa untuk menarik pelajaran dari pengalaman dan dokumenter untuk menciptakan pengalaman belajar yang beragam dan bermakna yang relevan dengan kehidupan sehari-hari mereka.